Analysis Level Physical Condition of Female Volleyball Athletes in Blitar City - Iqbal, Muhammad Iqbal Ferdy Septian; Khozanah Ilmah, Nur; Dwi Saputro, Yulianto; Nidomuddin, Muhammad; Pamungkas, Hari (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This study aimed to analyze the physical condition of female volleyball athletes in Blitar City. A total of 50 athletes from various clubs and teams were assessed using a battery of physical fitness tests, including BMI, Strength, Endurance,               Explosive power and Flexibility.The subjects of this research were 12 female athletes and received the same training program. Physical condition test for volleyball athletes based on BMI add up to 271.5 with an normal of 22.6 and ordinary category. Strength gets 551 comes about and an normal of 45.9 with the less category. Endurance is 380.6 with an normal of 31.7 and sufficient category. Explosive power totaled 589 with an normal of 49.1 within the adequate category. Flexibility totaled 493.4 with an normal of 41.1 and the category sufficient. BMI comes about get comes about with a rate of 58.3% within the typical category. Strength percentage is 41.6% within the less category. Continuance rate is 83.3% within the sufficient category. Explosive power comes about with a rate of 75% within the sufficient category. Flexibility with a rate of 66.6% within the sufficient category. Generally, the competitors appeared a moo level of physical wellness, with solid execution within the BMI, strength, flexibility, explosive power and endurance tests. In any case, there were varieties in execution levels among the competitors, demonstrating the require for individualized preparing programs.